Remodeling of Tumor Immune Microenvironment by Oncolytic Viruses - Zhang, Bin; Wang, Xilei; Cheng, Ping (Frontiers in Oncology, 2021)
Oncolytic viruses (OVs) are potential antitumor agents with unique therapeutic mechanisms. They possess the ability of direct oncolysis and the induction of antitumor immunity. OV can be genetically engineered to potentiate antitumor efficacy by remodeling the tumor immune microenvironment. The present mini review mainly describes the effect of OVs on remodeling of the tumor immune microenvironment and explores the mechanism of regulation of the host immune system and the promotion of the immune cells to destroy carcinoma cells by OVs. Furthermore, this article focuses on the utilization of OVs as vectors for the delivery of immunomodulatory cytokines or antibodies.